The hospice: Humane care for the dying - Franco, Vincent W. (Journal of religion and health, 1983)
The hospice movement arose as a reaction to the dehumanizing atmosphere of acute-care hospitals, where excessive utilization of life support equipment deprived dying patients of a meaningful vision of their destiny. Respecting the spiritual quest of the terminally ill for wholeness and dignity, the hospice concept prescribes the rendering of compassionate and pastoral care by a benevolent community of family, health care staff, friends, and clergy. Approximately 800 hospice programs are currently evolving in the United States. St. Mary's (formerly "Hillhaven") Hospice in Tucson, Arizona, offers the most comprehensive program of services, including home care, inpatient care, and artistic media through which the dying express their creativity. Numerous demonstration projects funded by several government agencies, principally the Health Care Financing Administration (HCFA), are expected to result in the legislative actions eliminating barriers to reimbursement of the cost of hospice services by Medicare, Medicaid, and other third-party payers. Existential analysis reveals the value of religion and spiritual support in enabling the dying to banish anxiety and muster the hope requisite for fully appreciating the authentic meaning of their destiny.